Strategy to Increase Creativity of Islamic Religious Education (PAI) Teachers in Utilizing Information Technology (IT)-Based Learning Media at State Junior High School 1 Kolaka - Adri, Adri; Hartono, Hartono; Zakariah, M. Askari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The background of this research is the importance of innovation in education in the digital age, where teachers are required to be highly creative in presenting lessons to enable more active and creative students. The primary focus of this research is to explore how the creativity of Islamic Religious Education (PAI) teachers can be enhanced through the use of Information Technology (IT)-based media. The problem formulation in this study is Creativity Enhancement Strategy: Islamic Religious Education teachers utilize IT-based learning media such as PowerPoint (PPT) and smartphones to create varied teaching materials. This strategy involves the use of creative applications such as Canva to design materials and CapCut or TikTok to document and publish student assignments. Forms of Creativity: Teacher creativity is manifested in two main forms, namely Ideas (unique thinking for learning solutions) and Products/Services (such as making explanatory videos, digital calligraphy, and educational content on social media). Impact and Constraints: The use of IT has been proven to increase student motivation and activeness in learning Islamic Religious Education, although there are still technical constraints in the form of unstable internet connections. This study employed qualitative methods with a descriptive approach. Data were collected through participant observation, in-depth interviews with the principal, Islamic Religious Education teachers, and students, and documentation. The study took place at SMP Negeri 1 Kolaka. The focus of the study included strategies for enhancing teacher creativity and the forms of creativity generated during the learning process. This study concludes that the creativity of Islamic Religious Education teachers at SMP Negeri 1 Kolaka is very important to motivate students to be more active and accelerate the achievement of learning objectives through the integration of relevant and innovative technology.